Fire and forest history of central European low mountain forest sites based on soil charcoal analysis: The case of the eastern Harz. (January 2014) - Robin, Vincent; Bork, Hans-Rudolf; Nadeau, Marie-Josée; Nelle, Oliver
Long-term environmental changes in some areas of Central Europe are still poorly documented due to the lack of archives suitable for well-established paleoecological approaches. However, paleorecords of such areas would provide important insights into the Holocene vegetation history of Central Europe. To contribute to fill this gap, we conducted soil charcoal analyses to investigate fire and forest history for the eastern Harz Mountains (Germany). Soil from 15 sequences at three investigation sites was analyzed, and charcoal assemblages were extracted. The taxonomic analysis shows Holocene woodland composition changes, from post-glacial pioneer woodland, dominated by pine, to broad-leaf closed forests, dominated by oak, and succeeded by beech. The temporal distribution of accelerator mass spectrometry (AMS)- 14 C datings of single charcoal pieces indicates that fire events occurred regionally synchronous, mainly in the late-Pleistocene/early-Holocene and late-Holocene periods. The radiocarbon dating is supported by the description of the sampled soil sequences, which permits the identification of late-Pleistocene/early-Holocene in situ formed soil horizons, as well as evidences late-Holocene erosion-sedimentation processes. Climate seems to have triggered late-Pleistocene/early-Holocene fire events. In contrast, the increase of fires, at both local and regional scales, during the late Holocene in low flammable broad-leaf forests is interpreted as related to human activities. Finally, it is highlighted that the species spectrum of the extracted charcoal assemblages and the radiocarbon ages obtained fits regional and over-regional data, also concerning the soil charcoal concentrations that appear to be included in regional and global ranges of soil charcoal pools.